Assessing Urban Characteristics: The C-DNA As a Catalyst of Urban Morphogenesis - Alsaffar, Noor Hadi; Abdullah, Sally Fakhri Khalaf; Alobaydi, Dhirgham; Hussein, Mohammed Mahdi; Al-Qaysi, Marwan A. J. (Salehan Institute of Higher Education, 2025)
Historic city centers are cultural archives where built forms and spatial practices hold the collective memory of generations. In Baghdad, the concept of Cultural DNA (C-DNA) is a tool to understand how cultural codes are the generative rules that shape the evolution and persistence of the historic urban fabric. This research explores the role of C-DNA as a trigger of urban morphogenesis in Rusafa, the historic heart of Baghdad, by looking into how cultural values underpin spatial continuity, change, and adaptability. The study uses Space Syntax methodologies with DepthmapX, supported by historical maps, surveys, and field observations, to analyze two morphological stages of Rusafa: 1850 and now. Through axial analysis, the research measures integration, connectivity, choice, and control to evaluate key urban characteristics: centrality, hierarchy, privacy, and territoriality. This comparative approach highlights both continuity and disruption in the historic fabric. The results show that cultural nuclei (mosques, markets, khans, and schools) are still the central points of the city, anchoring movement and interaction across centuries. Despite the disruption caused by modern interventions like Al-Rashid Street, the organic urban fabric still holds the capacity to sustain privacy, territoriality, and hierarchical spatial arrangements. The findings prove C-DNA is not a metaphor but an operational system that generates urban order and resilience. The study concludes that understanding C-DNA is crucial for developing sustainable revitalization strategies in Baghdad and similar Islamic historic cities. By treating culture as the city’s genetic code, planners and policymakers can design interventions that preserve cultural identity while accommodating urban needs.